How do you simplify [(x^3-3x^2)/ (3x+6)] / [(x^3-8x^2+15x) / (6x^2-18x-60)x33x23x+6x38x2+15x6x218x60?

1 Answer
Jul 20, 2015

I found: 2x(x+2)/(x+3)2xx+2x+3

Explanation:

I tried factorizing as much as possible to get (changing the division into a multiplication):

=(x^2(x-3))/(3(x+3))xx(6x^2-18x-60)/(x(x^2-8x+15))==x2(x3)3(x+3)×6x218x60x(x28x+15)=

=(x^2(x-3))/(3(x+3))xx(6(x+2)(x-5))/(x(x-3)(x-5))==x2(x3)3(x+3)×6(x+2)(x5)x(x3)(x5)=

=(x^cancel(2)cancel((x-3)))/(cancel(3)(x+3))xx(cancel(6)^2(x+2)cancel((x-5)))/(cancel(x)cancel((x-3))cancel((x-5)))=

=2x(x+2)/(x+3)